(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
Weather-climatic researches in the area of «Erebuni» Airport (Yerevan City) showed that cloud cover up to 500 m and lower is observed and can remain in following conditions: relative humidity of air is not less then 88%, the dew-point deficit to 4℃ and wind speed is 2–3 m/s with maximum to 5 m/s. The forecast of low cloud cover in the area of «Erebuni» Airport is made by synoptico-statistical method. Application of this method over very short range (up to 12 h) and nowcasting (from some minute to 3 h) the forecast provides about 80%, short-term (to 72 h) the forecast 70–75% were proved.